2020
DOI: 10.2196/16764
|View full text |Cite
|
Sign up to set email alerts
|

Embedding “Smart” Disease Coding Within Routine Electronic Medical Record Workflow: Prospective Single-Arm Trial

Abstract: Background Electronic medical record (EMR) chronic disease measurement can help direct primary care prevention and treatment strategies and plan health services resource management. Incomplete data and poor consistency of coded disease values within EMR problem lists are widespread issues that limit primary and secondary uses of these data. These issues were shared by the McMaster University Sentinel and Information Collaboration (MUSIC), a primary care practice-based research network (PBRN) locate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The usability of the CFS in primary care was evidenced in our study with frailty scores completed for 77% of eligible patients. This directly collected data was a strength of the study, as was the study setting within a PBRN where disease coding in the EMR has been strengthened through previous initiatives 25. We attribute the high scoring completion rate to a combination of factors: clinicians were engaged prior to deciding to go forward with the study; the study aligned with physicians’ interests in supporting frail patients as well as effective leadership and clinical championing of this study and its data collection requirements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The usability of the CFS in primary care was evidenced in our study with frailty scores completed for 77% of eligible patients. This directly collected data was a strength of the study, as was the study setting within a PBRN where disease coding in the EMR has been strengthened through previous initiatives 25. We attribute the high scoring completion rate to a combination of factors: clinicians were engaged prior to deciding to go forward with the study; the study aligned with physicians’ interests in supporting frail patients as well as effective leadership and clinical championing of this study and its data collection requirements.…”
Section: Discussionmentioning
confidence: 99%
“…There are 55 family physicians associated with the MUSIC Network. This study was based on a subset of the 37 physicians in the MUSIC PBRN, and their previously described 38 000 patients represent a broad cross section of patients 25 26…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians involved in patient care developed our smart tools, resulting in an EPT algorithm that was complementary to clinical workflow. Prior studies have demonstrated that longevity in EMR smart tools can be attributed to clinician involvement with the design and training for the workflow 21 …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that longevity in EMR smart tools can be attributed to clinician involvement with the design and training for the workflow. 21 STIs include trichomonas (n = 24), syphilis (n = 1), hepatitis b (n = 3), hepatitis C (n = 1), and HIV (n = 0). ¶ EPT was not known to be accepted or declined in n = 7 encounters before the intervention and n = 3 cases after the intervention because of unclear documentation and no evidence of prescription in the patient or partner's chart.…”
Section: Expedited Partner Therapymentioning
confidence: 99%